Pengaruh model Problem Based Learning berplatform Edmodo pada mata pelajaran Geografi terhadap kemampuan berpikir kritis siswa SMA - Indra Dwi Prasetya; Yusuf Suharto; Fatiya Rosyida; Hadi Soekamto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
Problem Based Learning has several advantages. First, the involvement or role of students is quite high. Both students became enthusiastic and interested in the learning process in working in groups. The purpose of this study was to determine the significant effect of the Problem Based Learning model with the Edmodo platform on the geography critical thinking skills of high school students. The research design used was Quasi Experimental with pretest-posttest design-control group. The subjects of this study were students of class XI IPS SMAN 1 Sukadana. Class XI IPS 1 as the experimental class and Class XI IPS 2 as the control class with 30 students per class. Data collection techniques obtained from critical thinking tests that have been tested for validity and reliability. The test questions are designed based on critical thinking indicators and geography material. Analysis using Mann-Whitney test with SPSS 22 for Windows. The results showed that the significance value of 0.000 less than 0.05 and the average value of the experimental class was greater (79.83) than the control class (67), which means that the Problem Based Learning model with the Edmodo platform in geography subjects has an effect on students' critical thinking skills. SENIOR HIGH SCHOOL. The most influential Problem Based Learning syntax is found in the syntax guiding individual and group investigations. In this syntax, students are required to collect data about a given problem. The results of this study can be developed with different research variables. Problem Based Learning memiliki beberapa keunggulan yang pertama keterlibatan atau peran siswa cukup tinggi. Kedua siswa menjadi semangat dan tertarik dalam proses pembelajaran pada pengerjaan secara berkelompok. Tujuan penelitian ini adalah untuk mengetahui pengaruh yang signifikan model Problem Based Learning berplatform Edmodo terhadap kemampuan berpikir kritis geografi siswa SMA. Desain penelitian yang digunakan adalah Quasi Experimental dengan pretest-posttest design-control group. Subjek penelitian ini adalah siswa kelas XI IPS SMAN 1 Sukadana. Kelas XI IPS 1 sebagai kelas eksperimen dan Kelas XI IPS 2 sebagai kelas kontrol dengan jumlah siswa per kelas 30 orang. Teknik pengumpulan data diperoleh dari tes berpikir kritis yang telah diuji validitas dan reliabilitas. Soal-soal tes dirancang berdasarkan indikator berpikir kritis dan materi geografi. Analisis menggunakan uji Mann-Whitney dengan SPSS 22 for Windows. Hasil penelitian menunjukkan bahwa nilai signifikansi 0,000 kurang dari 0,05 dan nilai rata-rata kelas eksperimen lebih besar (79,83) dibandingkan kelas kontrol (67), yang berarti model Problem Based Learning berplatform Edmodo pada mata pelajaran geografi berpengaruh terhadap kemampuan berpikir kritis siswa SMA. Sintak Problem Based Learning yang paling berpengaruh terdapat pada sintak membimbing penyelidikan individu maupun kelompok. Pada sintak tersebut siswa dituntut mengumpulkan sebuah data mengenai permasalahan yang diberikan. Hasil penelitian ini dapat dikembangkan dengan variabel penelitian yang berbeda.